Identifikasi Jenis Gastropoda Conus spp. di Perairan Pesisir Manokwari - Karubuy, Randy Imanuel Sandy; Manan, Jemmy; Manangkalangi, Emmanuel; Sembel, Luky; Saleky, Dandi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Gastropods Conus spp. is a macrozoobenthic organism that is abundant in coastal waters and is consumed by coastal communities. Conus is a carnivorous organism that lives permanently at the bottom of the waters and has the property of accumulating pollutant materials such as pesticides, carbonates and heavy metals into the body's tissues through the food chain. The aim of this study was to identify the gastropods species Conus spp. from the Manokwari Coastal Waters. The available research method is quantitative descriptive research. The target species in this study were gastropods of the genus Conus spp. collected from the Manokwari Coastal Waters. A total of 27 individuals from 6 species of Conus spp. collected from 3 observation stations. Gastropods Conus spp. 6 species were found, namely: 1) Conus leopardus; 2) Conus imperialis; 3) Conus eburneus; 4) Conus virgo; 5) Conus planorbis, and 6) Conus lividus. The air quality parameters measured were within the appropriate range for the Gastropods Conus spp.